2016
DOI: 10.1111/jcpp.12652
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Randomized controlled trial of vitamin D supplementation in children with autism spectrum disorder

Abstract: This study is the first double-blinded RCT proving the efficacy of vitamin D3 in ASD patients. Depending on the parameters measured in the study, oral vitamin D supplementation may safely improve signs and symptoms of ASD and could be recommended for children with ASD. At this stage, this study is a single RCT with a small number of patients, and a great deal of additional wide-scale studies are needed to critically validate the efficacy of vitamin D in ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 31 publications
1
45
0
2
Order By: Relevance
“…Low-level evidence based on a single case report25 and two open-label studies support the role of vitamin D supplementation in ASD 26 27. Additionally, a single, double-blind, randomised, placebo-controlled trial reported benefit of supplementation in ASD 28. However, any potential mechanisms mediating a positive effect of vitamin D supplementation in ASD remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Low-level evidence based on a single case report25 and two open-label studies support the role of vitamin D supplementation in ASD 26 27. Additionally, a single, double-blind, randomised, placebo-controlled trial reported benefit of supplementation in ASD 28. However, any potential mechanisms mediating a positive effect of vitamin D supplementation in ASD remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of ASD is not known but multifactorial, based on the interplay of genetic predisposition and environmental influences. Among the environmental influences, recent studies report that Vitamin D deficiency is common in children with autism and its correction improves their behavior [2].…”
Section: Discussionmentioning
confidence: 99%
“…A case report [147], along with open and controlled trials [142,148], observed an ASD symptom scores reduction after vitamin D 3 supplementation. However, recent placebo-controlled clinical trials have found divergent results following vitamin D 3 supplementation for ASD [149,150].…”
Section: Supplementsmentioning
confidence: 99%